QUALITY BY DESIGN DRIVEN FORMULATION DEVELOPMENT AND OPTIMIZATION OF POOR SOLUBLE ANTI-HYPERTENSIVE DRUG FOR IMPROVED SOLUBILITY - AGGARWAL, DEEPTI; GUPTA, RAM DAYAL; SHARMA, VIJAY (International Journal of Applied Pharmaceutics, 2025)
Objective: The objective of this study was to develop a polymeric composite of the poorly soluble antidepressant drug felodipine with help of PVP K-30 and PEG 6000, using a Quality by Design (QbD) approach to enhance its solubility and, consequently, its bioavailability. Methods: In this work, the quality target product profile (QTTP) was defined and Critical Quality Attributes (CQAs) were identified. Additionally, risk assessment analyses were carried out using the Ishikawa fishbone diagram to identify the Critical Material Attributes (CMAs) and/or Critical Process Parameters (CPPs) associated with the development of polymeric composite that could influence the Critical Quality Attributes (CQAs) of the drug product. The solubility of felodipine hydrochloride was improved by creating various polymeric composites with various concentrations of Poly Vinyl Pyrrolidone K30 (PVP-K 30) and Poly Ethylene Glycol 600 (PEG 600) by solvent evaporation method as Critical material attribute (CMA) as identified by risk assessment study and the and CQAs viz drug solubility, drug content and drug release. These composites were designed using a 32 Face Central composite Design (FCCD) with a face-centered approach implemented in Design Expert software. Results: After defining QTTP and CQA, risk assessment analysis was successfully used to identify CMA as well as CPPs. A total of thirteen PVP-PEG polymeric composites were developed and evaluated for FTIR spectra, Differential Scanning Colorimetry (DSC), X-Ray diffraction (XRD), and Scanning electron Microscopy (SEM). Data optimization was performed using response surface methodology, including contour and overlay plots. Solubility, drug content, and drug release of the optimized batch were found to be 21.55 mg/ml, 100%, and 78.314%, respectively. Three Validation Check batches (VC1-VC3) were developed and validated. Percent error for solubility ranges between-0.0019 to 0.0061, drug content ranges between 0.0005 to 0.0031 and solubility ranges between 0.0005 to 0.0011 that were very close to the predicted value, hence verifying the optimized data. Thus, by carefully using the QbD technique, the solubility of felodipine was enhanced by the effective development of a PVP-PEG polymeric composite. Conclusion: The QbD approach was to be an effective tool to develop an optimized polymeric composite of PVP 30K and PEG 6000 of felodipine with improved solubility without exhaustive research.